Identifying factors affecting the pharmacokinetics of voriconazole in patients with liver dysfunction: A population pharmacokinetic approach. Issue 1 (27th February 2019) - Tang, Dan; Song, Bai‐Li; Yan, Miao; Zou, Jian‐Jun; Zhang, Min; Zhou, Hua‐Ying; Wang, Feng; Xiao, Yi‐Wen; Xu, Ping; Zhang, Bi‐Kui; Chen, Xi‐Jing; Xiang, Da‐Xiong; et al.
Abstract: Voriconazole is a broad‐spectrum antifungal agent commonly used to treat invasive fungal infections. Voriconazole has significant intraindividual and interindividual pharmacokinetics variability in different patient populations. Pharmacokinetic data of voriconazole in patients with liver dysfunction were limited. The aims of this study were to evaluate the population pharmacokinetics of voriconazole in patients with liver dysfunction and to identify the factors that affect voriconazole pharmacokinetics. A total of 166 samples taken from 57 patients with liver dysfunction were included in the study. A one‐compartment pharmacokinetic model with first‐order absorption and elimination was used to describe the data. Voriconazole clearance (CL) was 0.58 L/h, the volume of distribution ( V d ) was 134 L, and oral bioavailability ( F ) was 80.8%. This study showed that platelet count was significantly associated with voriconazole pharmacokinetic parameters. CYP2C19 polymorphisms had no effect on voriconazole pharmacokinetic parameters. Voriconazole CL was significantly decreased in patients with liver dysfunction. This study provides useful pharmacokinetics information for patients with liver dysfunction while highlighting the value of therapeutic drug monitoring in adjusting doses.